Is technology-mediated learning made equal for all? Examining the influences of gender and learning style - Hu, P.; Hui, Wendy (Sense Publishers, 2011)
The current research investigates the equality of students’ learning outcomes in technology-mediated learning. We study important individual differences and focus on the influences of gender and learning style. We perform two experimental studies that employ methodologically rigorous designs, multiple learning outcome measures, and previously validated measurement scales. Specifically, we examine learning effectiveness, perceived learn ability, and learning satisfaction in technology mediated learning, using classroom-based face-to-face learning as a comparative baseline. Our investigations address some limitations commonly found in many prior studies, including instrument reliability and confounding factors. Overall, our findings suggest that students benefit from technology-mediated learning differently, dependent on their gender. For example, female students consider technology-mediated learning more effective and satisfactory than male students, but their learning motivation is significantly lower than that of their male counterparts. Learning style also matters, perhaps to a lesser extent. Students who rely more on concrete experience, as opposed to abstract conceptualization, find the course materials delivered through technology-mediated learning more difficult to learn. Our findings have several implications for research and practice, which are discussed.